Mathematwist : number tales from around the world - "Padma, T. V. (T. Venkataraman), 1969-" (Chennai, 2017)
This book define, what could Caesar's general have in common with multiplication and weights? Or a Russian waiter with factorials? Or a temple in Hanoi with transposition? A Chinese emperor with Benjamin Franklin and Albrecht Duerer? This book is a collection of stories from different countries. Each story sets the brain ticking, encouraging problem-solving skills, with a high quotient of fun! and each is followed by a simple explanation of the maths behind the 'magic', that dispels the esoteric haze from the subject and makes it accessible. A fascinating collection about mathematics and the world, from a country that has been prominent on the number map from ancient times.
Keywords: Children Books